Language Proficiency of Migrants: The Relation with Job Satisfaction and Skill Matching - Hans G. Bloemen (Tinbergen Institute, 2014)
We empirically analyze the language proficiency of migrants in the Netherlands. Traditionally, the emphasis in studying language proficiency and economic outcomes has been on the relation between earnings and indicators for language proficiency, motivated by the human capital theory. Here we analyze whether there is a relation between proficiency of the destination language and job level. A lack of language skills may induce the migrant to work in jobs of a lower level leading to lower job satisfaction. We use subjective survey information about job satisfaction and the fit between the migrant's education and skill level and the job. We also use objective information on professional level. Our estimation strategy allows for unobservable correlations between language proficiency and labour market outcomes by employing a simultaneous two equations framework which also exploits the panel nature of our data, by allowing for time persistent random effects. We use a variety of different instrumental variables, some of which are related to linguistic distance, to shed light on the robustness of the results. For men, we find evidence for a positive relationship between indicators for language proficiency and satisfaction with work type and professional level. For women, no impact of language proficiency on the level of the job can be found. Rather, women with lower proficiency levels are not selected into employment in the first place.
Keywords: J15; J24; C33; 330; Skills; Occupational choice; Economics of Immigrants; Panel data models